The Effect of Sponsorship Disclosure in YouTube Product Reviews. Issue 4 (2nd October 2021) - Pfeuffer, Alexander; Lu, Xinyu; Zhang, Yiran; Huh, Jisu
Abstract: Facing the rising trend of sponsored product reviews posted on social media, government regulatory agencies have published industry guidelines requiring disclosure of sponsorship in social media product reviews. However, research about the effects of online product review sponsorship disclosures, especially in the social media context, is still limited. To address this problem, the current study tested the effects of sponsorship disclosure in YouTube product reviews on consumers' persuasion knowledge and attitudinal responses to the product, brand, and the reviewer. Persuasion Knowledge Model and expectancy violations theory were applied to form the theoretical foundation for the study hypotheses. Results from an online experiment revealed: (1) sponsorship disclosure increased consumers' perceived persuasive intent and appropriateness of a sponsored product review but not their perceived effectiveness of the content; (2) sponsorship disclosure had no significant effect on viewers' attitudes toward the reviewed product, brand, or the reviewer; and (3) viewers' expectancy moderated the effects of sponsorship disclosure on persuasion knowledge. Implications of the study findings and limitations and suggestions for future research are discussed.